Factors Associated With Increased Hospital Length of Stay in Peritoneal Dialysis Patients With Peritonitis: A Need for Antimicrobial Stewardship?. (February 2020) - Morrisette, Taylor; Canada, Robert B.; Padgett, Danielle; Hudson, Joanna Q.
Background: Peritonitis remains a complication of peritoneal dialysis (PD) and contributes to morbidity. Adherence to evidence-based recommendations should resolve peritonitis within 5 days; however, hospital length of stay (LOS) for patients with PD-associated peritonitis (PDAP) varies. Factors contributing to increased LOS and vigilance with antimicrobial stewardship (ASP) in this population are not well described.Methods: This was a system-wide, retrospective cohort of adult patients presenting with PDAP from August 2012 to August 2017. Patients were divided into 2 groups based on LOS: <7 days (reduced LOS) versus ≥7 days (prolonged LOS). Patient demographics, resolution of peritonitis by day 5, intensive care unit (ICU) admission, infectious diseases (ID) consultation, changes in dialysis modality, blood glucose, and pathogen/antimicrobial characteristics were compared. In-hospital mortality and 30-day readmissions were also evaluated.Results: Of the 401 patients screened, 90 were included: 53% women, 88% African American, age 52 ± 2 years (reduced LOS: 46 patients; prolonged LOS: 44 patients). Increased LOS was associated with ICU admission ( P = .014), ID consultation ( P = .015), PD catheter removal ( P = .001), hemodialysis conversion ( P < .001), antifungal therapy ( P = .021), and days with blood glucose >180 mg/dL ( P = .028). Opportunities for antimicrobial de-escalation were identified in 24 (52%) and 22 (50%) patients in the reduced and prolonged LOS groups, respectively; however, de-escalation occurred in only 5 (21%) and 6 (27%) of these patients. There were no differences in mortality or 30-day readmissions.Conclusions: Longer LOS was influenced by acuity of illness and possibly lack of enforced ASP. Improvement of ASP within the PDAP population is necessary.